Antioxidant and Antidiabetic Potential of Bryophyllum pinnatum Leaf Extract In Vitro - Ogunmoyole, Temidayo; Odunyemi, Praise Ololade; Akeem, Yusuff Adewale; Johnson, Olaitan Daniel; Adefila, Adenike Oluwaseun; Ogundare, Aderonke Mary (European Journal of Applied Sciences, 2025)
Bryophyllum pinnatum has been traditionally used in folkloric medicine for various treatments. This study investigates the antioxidant and antidiabetic properties of B. pinnatum leaf extract as a potential management option for diabetes. The free radical scavenging ability of B. pinnatum leaf extract was evaluated against 2, 2-diphenyl-1-picrylhydrazyl (DPPH, hydrogen peroxide, and nitric oxide (NO) radicals in vitro following established protocols. Ferric reducing antioxidant power (FRAP), lipid peroxidation, and iron (II) chelating ability of the leaf extract were also measured in vitro. The inhibitory effects of the extract on key carbohydrate-metabolizing enzymes, including α-amylase and α-glucosidase, were also determined as an index of its potential antidiabetic properties following standard procedures. The total phenolic and flavonoid content of the leaf extract was also quantified. The bioactive constituents of the leaf extract were also profiled using Gas Chromatography-Mass Spectrometry (GC-MS). The results indicated that B. pinnatum leaf extract demonstrated significant free radical scavenging activity against DPPH, hydrogen peroxide, and NO. The extract also showed marked ferric reducing power, iron chelating ability, and inhibition of lipid peroxidation. The extract exhibited potent inhibitory effects on α-amylase and α-glucosidase, with IC50 values of 2.78 µg/ml and 0.65 µg/ml, respectively, suggesting its in vitro antihyperglycemic potential. Twenty-eight (28) phytochemicals were profiled from the GC-MS chromatogram. The presence of these bioactive compounds in the plant might explain its relevance in managing diabetes in folkloric medicine.